Recent developments in aviation law. - KENNEY, Stephen C. (1995)
Presents a report of aviation case law decisions from all United States jurisdictions that were published between November 1, 1993 and December 1994. Includes a selection of cases outside of the aviation context that may have significant effects in future aviation cases. Summarizes relevant statutory enactments, including the General Aviation Revitalization Act of 1994.